ARTISTIC AND FUNCTIONAL FEATURES OF THE CHRONOTOPE (SPATIAL CONFIGURATION) IN RUSSIAN AND UZBEK LITERARY STUDIES - Grigoryeva Mariya Vitalyevna (Modern American Journals, 2025)
The article examines the artistic and functional characteristics of the chronotope (spatial-temporal configuration) in Russian and Uzbek literary studies. The chronotope, introduced by M. Bakhtin as a category expressing the intrinsic interconnection of time and space in artistic discourse, plays a central role in shaping narrative structure, character development, and ideological meaning. By comparing Russian and Uzbek literary traditions, the study analyzes how different cultural, historical, and aesthetic determinants influence the representation of space and time in literature. Special attention is given to the functions of the chronotope in classical and modern works, including its role in reflecting national identity, social transformations, mythopoetic worldviews, and artistic symbolism.
Keywords: Chronotope; space and time; spatial configuration; Russian literature; Uzbek literature; literary semantics; narrative structure; national identity; cultural worldview; artistic poetics; Bakhtinian theory; mythopoetics.